Design and simulation of metal PBG waveguide mode launcher - Thottappan M.; Jain P.K. (My University, 2025)
The design and simulation of a metal Photonic Band Gap (MPBG) cylindrical waveguide to a conventional rectangular waveguide transition using a wraparound co-axial coupler is presented. A rectangular waveguide drives a combined wraparound co-axial / MPBG cylindrical waveguide system. The wraparound co-axial input coupler converts a dominant rectangular waveguide mode into a resonator mode and which is then coupled into the MPBG waveguide for the desired circular mode. A typical wraparound coaxial coupler for exciting a Kaband MPBG waveguide has been designed. The structure has been simulated using 3-D electromagnetic code 'CST Microwave studio'. Its Eigen mode simulation ensures that the RF magnetic field coupling into the co-axial waveguide through five azimuthally spaced apertures. Further, this simulation shows the confinement of the desired TE01-like mode in the defect portion of the MPBG triangular lattice structure and ensures that the all other competing spurious modes are suppressed. The transient analysis has also been preformed and it confirms the mode propagation in PBG waveguide through the calculation of insertion loss. The coaxial coupler offers a return loss and insertion loss of-30 dB and-0.5 dB respectively at 35 GHz with a wide bandwidth about ∼ 6 %. © 2014 IEEE.